Case report: Paralytic ileus resulted from nirmatrelvir/ritonavir-tacrolimus drug-drug interaction in a systemic lupus erythematosus patient with COVID-19 - Zhang, Wei; Zhang, Xingguo; Han, Jinming; Zhang, Wen; Xu, Jiarui; Zhang, Xin; Bian, Hongjun; Meng, Chong; Shang, Deya; Zhou, Yi; Wang, Dawei; Feng, Baobao (Frontiers in Pharmacology, 2024)
Patients with systemic autoimmune rheumatic diseases (SARD) are at a high risk for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and effective antiviral treatments including nirmatrelvir/ritonavir can improve their outcomes. However, there might be potential drugdrug interactions (DDIs) when these patients take nirmatrelvir/ritonavir together with immunosuppressants with a narrow therapeutic window, such as tacrolimus and cyclosporine. We present a case of paralytic ileus resulting from tacrolimus toxicity mediated by the use of nirmatrelvir/ritonavir in a patient with systemic lupus erythematosus (SLE). A 37-year-old female SLE patient was prescribed nirmatrelvir/ritonavir without discontinuing tacrolimus. She presented to the emergency room with symptoms of paralytic ileus including persistent abdominal pain, nausea, and vomiting, which were verified to be associated with tacrolimus toxicity. The blood concentration of tacrolimus was measured > 30 ng/mL. Urgent medical intervention was initiated, while tacrolimus was withheld. The residual concentration was brought within the appropriate range and tacrolimus was resumed eight days later. Physicians must be aware of the potential DDIs when prescribing nirmatrelvir/ritonavir, especially to those taking immunosuppresants like tacrolimus.